Analisis Asumsi Hubungan Mengalami Kemajuan dalam Pola Komunikasi Keluarga pada Drama Korea The Good Bad Mother 2023 - Anggoro, Melinda; Claudya, Samantha; Hardiyarso, Stevanus (Jurnal PIKMA : Publikasi Ilmu Komunikasi Media Dan Cinema, 2024)
Drama is a form of social reality and elevates the reality of society. The drama tells about the family. The family is the first place for children to communicate. Parents play an important role in educating and determining the child's future. In family communication, children get different communication patterns, namely: authoritarian, democratic, and permissive. This phenomenon is found in the Korean drama The Good Bad Mother 2023. The drama is a family drama that tells the story of a mother educating her son hard to succeed in becoming a prosecutor. The child succeeds in becoming a prosecutor and has an accident that paralyzes his entire body and only remembers at the age of seven. Their relationship restarts from non-intimate to intimate. This research is a qualitative research with content analysis method. Data collection techniques with observation and documentation of episodes three and four. The findings in this study show that Young Soon uses authoritarian communication patterns in episode three and their relationship progresses from intimate to intimate.